Financial Technology and Service Quality for Purchasing Decisions Through Customer Trust in Indonesian State-Owned Enterprise (BUMN) - Syahrul Daffa, Mohammad; Maolana Hidayat, Agus (Universitas Medan Area, 2024)
The rapid progress of the internet and technology continues to unfold, giving rise to innovations in various sectors dependent on these advancements. Financial technology is one such evolving technology in the current landscape. According to the theory, financial technology is defined as the application of technology aimed at enhancing the value of financial services and has the potential to increase customer trust through the development and provision of products. However, specific research on financial technology remains scarce. The focus of this research is to assess the influence of financial technology and service quality on purchasing decisions through customer trust. The research methodology employs a quantitative approach with the distribution of questionnaires. The sample for this study consists of 360 respondents, and the data analysis technique used is Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of this study indicate that financial technology and customer trust significantly and positively impact purchasing decisions. Service quality also has a positive and significant effect on customer trust and purchasing decisions. However, financial technology and purchasing decisions do not exhibit a significant positive impact. The inclusion of the customer trust variable is considered crucial as it can mediate relationships with other variables.